Neutral Polysaccharides From Hohenbuehelia serotina With Hypoglycemic Effects in a Type 2 Diabetic Mouse Model - Qinghong Liu; Jing Wu; Peng Wang; Yuxiao Lu; Xinhe Ban (Frontiers in Pharmacology, 2022)
Neutral polysaccharides (NHSPs) from the mushroom Hohenbueheliaserotina were purified by D301/D152 resin ion-exchange chromatography and DEAE-cellulose anion exchange chromatography. The weight-average molecular weight (MW) and number-average molecular weight (Mn) of NHSP were 1,821 and 820.55 kDa, respectively. A monosaccharide component analysis showed that NHSP was composed of glucose, galactose, and mannose in molar ratio 2.6:2.1:1.0. FT-IR and NMR (1H and HSQC) spectroscopic analyses revealed that NHSP contained mainly 1,3-linked β-D-glucose, 1,4-linked β-D-glucose, 1,6-linked β-D-mannose, 1,6-linked α-D-mannose, and 1,6-linked β-D-galactose. The thermogravimetric analysis (TGA) showed that NHSP has good thermal stability below 250°C. NHSP notably reduced the blood glucose level (hypoglycemic effect) at dose 200 mg/kg for 21 days in a type 2 diabetic mouse model. NHSP reduced the liver index significantly, suggesting that it may help prevent hepatic steatosis or hepatomegaly.